Peran lembaga informasi dalam era post-truth - Faturahmi, Nurul Ivar (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. The role of information institutions in the post-truth era is important in creating an independent and competent society in dealing with information. This conceptual article aims to see the role of information institutions in responding to community information behavior in the post-truth era. Data Collection Method. The method in this article uses a qualitative approach with the type of narrative review. Data Analysis. The analysis was carried out by synthesizing the literature and case studies from several reports discussing the impact of fake news spread in the community. Results and Discussions. Information institutions need to take an active role in improving the conditions of society through knowledge-based development and information sharing processes, to create a community that is capable in using information and in evaluating the credibility and suitability of information sources. Conclusion. In the post-truth era, psychological aspects become an important aspect, where one's information behavior becomes more dominantly influenced by emotional dimensions and personal beliefs. This increasingly shows the importance of skills in evaluating information sources and critical thinking more clearly than in previous eras.